(untitled) (Philological Studies, 2019)
The relevance of the work is due to the appeal to the analysis of microtoponymy of Perm region, what is not deeply explored. The paper discusses language models for the expression of spatial relationships on the basis of the Permian toponymy. The author dwells on the characteristics of the spatial model «top / bottom». The article defines the main indicators of the location of the object on a vertical line. These indicators most often become the definition of top (верхний) / bottom (нижний), high (высокий) / low (низкий). The spatial model "top / bottom" can be implemented using prepositional case constructions that include prepositions выше, ниже, над, под. The idea of the location above / below the ground plane is also reflected in microtoponyms, which include geographic terms that call positive and negative objects of relief. One of the ways to reflect the position of an object in space is metaphorical names, which in Perm microtoponymy most often refer to elevations.